1993
DOI: 10.1097/00000658-199307000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Cytokines After Thermal Injury and Their Relationship to Infection

Abstract: These results suggest that IL6 and TNF alpha play a role in the response of burned patients to infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
1
2

Year Published

1994
1994
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(41 citation statements)
references
References 12 publications
2
36
1
2
Order By: Relevance
“…Burn injury appears to prime macrophages to subsequent stimulation as evidenced by increased production of inflammatory mediators such as TNF-␣, IL-6, nitric oxide, and PGE 2 [7][8][9]. Macrophage hyperactivity, defined as the increased productive capacity for inflammatory mediators, has been implicated in the increased susceptibility to sepsis after thermal injury.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Burn injury appears to prime macrophages to subsequent stimulation as evidenced by increased production of inflammatory mediators such as TNF-␣, IL-6, nitric oxide, and PGE 2 [7][8][9]. Macrophage hyperactivity, defined as the increased productive capacity for inflammatory mediators, has been implicated in the increased susceptibility to sepsis after thermal injury.…”
Section: Discussionmentioning
confidence: 99%
“…This immune dysfunction following thermal injury appears to involve multiple factors, including T lymphocyte dysfunction [4,5], increased levels of Th-2 cytokines [i.e., interleukin (IL)-4, IL-10] [6], and increased production of macrophage inflammatory mediators [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from clinical studies as well as animal models of trauma and sepsis have shown that elevations in IL-6 production can be directly correlated with suppressed cellular immune responses and overall poor clinical prognosis [8][9][10]. Several different cell types are capable of producing IL-6, including fibroblasts, lymphocytes, and cells of the monocyte/ macrophage lineage.…”
Section: Introductionmentioning
confidence: 99%
“…Associam-se, especialmente nos casos graves, a APR, com os conseqüentes aumentos de níveis circulantes de citocinas, como a IL-6 e o TNF-α 49 . A IL-2 tem seus níveis reduzidos 50 .…”
Section: Resposta Ao Trauma E Cirurgiaunclassified